If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 40 = 13x + -68 Reorder the terms: 40 + 4x = 13x + -68 Reorder the terms: 40 + 4x = -68 + 13x Solving 40 + 4x = -68 + 13x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13x' to each side of the equation. 40 + 4x + -13x = -68 + 13x + -13x Combine like terms: 4x + -13x = -9x 40 + -9x = -68 + 13x + -13x Combine like terms: 13x + -13x = 0 40 + -9x = -68 + 0 40 + -9x = -68 Add '-40' to each side of the equation. 40 + -40 + -9x = -68 + -40 Combine like terms: 40 + -40 = 0 0 + -9x = -68 + -40 -9x = -68 + -40 Combine like terms: -68 + -40 = -108 -9x = -108 Divide each side by '-9'. x = 12 Simplifying x = 12
| r+33=14 | | -2t^2-6t+5=0 | | 5y-2+y+48=5y+50-1y | | 5x=165 | | 6x+34=14x+30 | | 3x+139=2x+26 | | y+25y-15y-9y=15-15 | | 2S=2Vt-gt^2 | | 5+x=(3+19x) | | 31+3x=34 | | 6x^2+4x=240 | | 9x+15-7x+15=-2 | | -113=5(5p+3)-3 | | s-44=-13 | | -4(x+5)+3=6(x+4)+1 | | f/2-19=-17 | | 8x-12=68 | | 6q=-6+7q | | 8x=6x+14 | | 5.85=0.65x | | -8=-(v+4) | | -7+6r=6r+3+r | | 8x-(x+3)(4x-5)=(5+2x)(4-x)-3(x+4) | | 6(8+3x)=174 | | 6y-25=4y+2 | | 17-9x=11+7x | | 69-7x=2x+23 | | h(t)=-16x^2+14 | | -160=8(4m-4) | | 9-7x=113-35x | | -5+5f=-5+8f | | 13x+9=15x-1 |